The First Public Murder in the Tanzimat Era: Life, Trial and Execution of Emine Hanim - Siviloglu, Murat (My University, 2023)
In 1860, Emine Hanım killed her husband Ferik İbrahim Pasha. In this article, I use her murder trial to examine the interrelation between slavery, the private lives of the Ottoman ruling class, and the complexities of the judicial system during the Tanzimat period (1839–1876). I identify the limitations of nineteenth-century legal reforms and the discrepancy between the reformist ideals and the real-world complexities experienced by individuals. By paying close attention to legal issues in the Ottoman Empire during the Tanzimat era, such as siyaseten katl (administrative death penalty) and the inconsistent application of kısas (retaliation in kind), I argue that Emine’s story contributes to a better understanding of the Ottoman legal system during the reform era.
PUBLISHED
Keywords: Tanzimat – Ottoman law – Islamic law – kısas – Ferik İbrahim Pasha – Namık Kemal – Mehmed Sadık Pasha – siyaseten katl – slavery; Digital Humanities; Identities in Transformation; Manuscript, Book and Print Cultures; Gender; History